SIGNIFICANCE OF THE G-197A POLYMORPHISM OF THE IL17A GENE IN THE FORMATION OF VITILIGO - Yakubova Azizakhon Saidkasimovna (Scholar Express Journals, 2021)
Vitiligo is a multifactorial disease, and the destruction of melanocytes develops as a result of genetic mutations, immune and autoimmune reactions, oxidative stress, neuroendocrine changes, the formation of inflammatory mediators, etc. In recent years, the attention of scientists has been attracted by the participation of a relatively new interleukin-17 (IL-17) in the pathogenesis of some immune-mediated autoimmune diseases, including vitiligo. However, in the literature, the significance of this cytokine is not clearly defined and the data are contradictory. A number of scientific studies have noted an increase in IL-17 in the blood and tissue samples of vitiligo patients compared with control subjects (p = 0.001) and positively correlated with the activity and area of the affected body surface. Whereas in other scientific work, the authors were unable to find a correlation between the level of IL-17 and the stage of the disease. To obtain a complete understanding of the studied cytokines, in particular IL-17, it is necessary to investigate the polymorphism of these genes, which will allow predicting the course and determine the effectiveness of therapy depending on the severity of alleles and genotypes of the studied genes in vitiligo patients. In this article, we present the results of a study of the G-197A polymorphism of the IL17A gene in the development of vitiligo in the Uzbek population.
Keywords: Vitiligo; IL17A Gene G-197A Polymorphism; Uzbek Population